A fluid inclusion record of magmatic/hydrothermal pulses in acid Salar Ignorado gypsum, northern Chile. Issue 3 (8th March 2016) - Karmanocky, F. J.; Benison, K. C.
Abstract: Salar Ignorado is a shallow acid saline lake hosted by a small intervolcanic basin high in the Andes Mountains of northern Chile. Modern surface waters have 3.3–4.1 pH, 0.5–3% total dissolved solids (TDS) and are actively precipitating gypsum crystals. The gypsum crystals trap the acid saline water as fluid inclusions, providing a record of recent surface water characteristics. Salar Ignorado gypsum contains three distinct types of primary fluid inclusions, which result from growth of the gypsum from surface waters. Petrography and microthermometry were performed on 27 gypsum crystals from Salar Ignorado to gain an understanding of recent water chemistry of the salar. One 18.3‐cm‐long gypsum crystal, hosting primary fluid inclusions along 28 successive growth bands, was the focus for fluid inclusion studies and allowed a record of high‐resolution chemical trends. This crystal showed a change in parent fluids during growth, from low salinity, to high salinity, back to low salinity. At the bottom of the crystal, the lowest six fluid inclusion assemblages have salinities of 1.7–5.1 eq. wt. % NaCl. The next nine fluid inclusion assemblages have significantly higher salinity (18.6–27.4 eq. wt. % NaCl) inclusions. The twelve fluid inclusion assemblages near the top of the crystal have low salinity (0.9–8.3 eq. wt. % NaCl) like those at the bottom of the crystal. The high‐salinity fluid inclusions in the middle of this gypsum crystal are interpreted to have formed during a pulse of magmatic/hydrothermal fluids to the surface, perhaps during local active volcanism. Secondary evidence of a magmatic influence on surface waters includes hydrogen sulfide and high molecular weight solid hydrocarbons within some fluid inclusions. This study is among the first detailed fluid inclusion studies of gypsum and suggests that fluid inclusions in gypsum can be paleo‐hydrogeologic proxies.